Hairy cell leukemia: A case report of unusual presentation without splenomegaly - Shuchismita .; Iffat Jamal; Vijayanand Choudhary (Medical Laboratory Journal)
Hairy cell leukemia (HCL) is characterized by pancytopenia and is usually associated with massive splenomegaly; however, the same may not be true in clinical settings. Here, we report a case of HCL without the classical clinical feature of splenomegaly. Absence of splenomegaly doesn’t exclude the diagnosis of HCL. A careful study of morphological findings on bone marrow aspirate and biopsy, followed by appropriate ancillary tests, aids in correct diagnosis. A high index of suspicion is essential for diagnosing and appropriately managing such cases. A strong suspicion on morphology in such cases is a prerequisite for reaching a correct diagnosis, even in the absence of usual clinical presentation.